2009
DOI: 10.1016/j.neuroimage.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of subjective perception of identity and expression in the face network: An fMRI adaptation study

Abstract: The recognition of facial identity and expression are distinct tasks, with current models hypothesizing anatomic segregation of processing within a face-processing network. Using fMRI adaptation and a region-of-interest approach, we assessed how the perception of identity and expression changes in morphed stimuli affected the signal within this network, by contrasting (a) changes that crossed categorical boundaries of identity or expression with those that did not, and (b) changes that subjects perceived as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
160
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(187 citation statements)
references
References 40 publications
25
160
2
Order By: Relevance
“…Lesions to this region can cause prosopagnosia 25 , the inability to recognize the identity of familiar individuals, while leaving the ability to detect the presence of a face intact. Numerous studies that have employed fMRI adaptation paradigms have demonstrated the sensitivity of the FFA to differences in face identity 21,[26][27][28][29][30] . In such paradigms the FFA shows a decreased response when one face stimulus is presented twice in rapid succession, when compared with the response when two novel stimuli are presented in the same manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesions to this region can cause prosopagnosia 25 , the inability to recognize the identity of familiar individuals, while leaving the ability to detect the presence of a face intact. Numerous studies that have employed fMRI adaptation paradigms have demonstrated the sensitivity of the FFA to differences in face identity 21,[26][27][28][29][30] . In such paradigms the FFA shows a decreased response when one face stimulus is presented twice in rapid succession, when compared with the response when two novel stimuli are presented in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…The STS contains patches of cells that are face-selective in monkeys 3,41 . In human neuroimaging repetition suppression studies the posterior portion of the STS is known to be sensitive to gaze direction and emotional expressions 42 , but also shows sensitivity to facial identities 21,28 . If the STS processes such a variety of different types of information about faces, what is its role is face perception?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional imaging studies in healthy subjects have identified a fusiform face area (FFA) in the lateral aspect of the fusiform gyrus that is activated more by faces than other objects [24][25][26], and which may be involved in discriminating the structural aspects of faces relevant to facial identity [27]. Prosopagnosic patients with right fusiform lesions are impaired in the perception of facial structure, especially the configuration or spatial arrangement of features within a face [28].…”
Section: Introductionmentioning
confidence: 99%
“…The role of these different regions is controversial. Thus, a hierarchy has been proposed between the Occipital cortices, which show sensitivity to physical properties of a face (Pitcher, Walsh & Duchaine, 2011), and the FFA that could be involved in perceiving identity (Fox, Moon, Iaria & Barton, 2009). However, Rossion, Caldara, Seghier, Schuller, Lazeyras & Mayer (2003) and Rossion (2008), have proposed a reverse hierarchical model of face perception, which assumes that re-entrant, interactions may also exist between FFA and lower order (OFA) visual areas.…”
mentioning
confidence: 99%